Nanoimprint Lithography Facilitated Plasmonic‐Photonic Coupling for Enhanced Photoconductivity and Photocatalysis. (29th June 2021) - Gupta, Vaibhav; Sarkar, Swagato; Aftenieva, Olha; Tsuda, Takuya; Kumar, Labeesh; Schletz, Daniel; Schultz, Johannes; Kiriy, Anton; Fery, Andreas; Vogel, Nicolas; König, Tobias A. F.
Abstract: Imprint lithography has emerged as a reliable, reproducible, and rapid method for patterning colloidal nanostructures. As a promising alternative to top‐down lithographic approaches, the fabrication of nanodevices has thus become effective and straightforward. In this study, a fusion of interference lithography (IL) and nanosphere imprint lithography on various target substrates ranging from carbon film on transmission electron microscope grid to inorganic and dopable polymer semiconductor is reported. 1D plasmonic photonic crystals are printed with 75% yield on the centimeter scale using colloidal ink and an IL‐produced polydimethylsiloxane stamp. Atomically smooth facet, single‐crystalline, and monodisperse colloidal building blocks of gold (Au) nanoparticles are used to print 1D plasmonic grating on top of a titanium dioxide (TiO2 ) slab waveguide, producing waveguide‐plasmon polariton modes with superior 10 nm spectral line‐width. Plasmon‐induced hot electrons are confirmed via two‐terminal current measurements with increased photoresponsivity under guiding conditions. The fabricated hybrid structure with Au/TiO2 heterojunction enhances photocatalytic processes like degradation of methyl orange (MO) dye molecules using the generated hot electrons. This simple colloidal printing technique demonstrated on silicon, glass, Au film, and naphthalenediimide polymer thus marks an important milestone for large‐scale implementation in optoelectronic devices. Abstract : Nanoimprint lithography facilitates the fabrication of large‐scale hybrid optoelectronic devices using colloidal ink. The feasibility of scaling is explored in full‐depth by a successful arrangement of diffractive plasmonic grating over photonic waveguide slabs toward the generation of waveguide‐plasmonic polariton modes. Marked by its characteristic anti‐crossing nature, such modes are verified via photoresponse measurements and are utilized for photocatalytic applications.